Rewiring the T cell-suppressive cytokine landscape of the tumor microenvironment: a new frontier for precision anti-cancer therapy - Lopresti, Ludovica; Tatangelo, Vanessa; Baldari, Cosima T.; Patrussi, Laura (Frontiers in Immunology, 2024)
T lymphocytes that infiltrate the tumor microenvironment (TME) often fail to function as effective anti-cancer agents. Within the TME, cell-to-cell inhibitory interactions play significant roles in dampening their anti-tumor activities. Recent studies have revealed that soluble factors released in the TME by immune and non-immune cells, as well as by tumor cells themselves, contribute to the exacerbation of T cell exhaustion. Our understanding of the cytokine landscape of the TME, their interrelationships, and their impact on cancer development is still at its early stages. In this review, we aim to shed light on Interleukin (IL) -6, IL-9, and IL-10, a small group of JAK/STAT signalingdependent cytokines harboring T cell-suppressive effects in the TME and summarize their mechanisms of action. Additionally, we will explore how advancements in scientific research can help us overcoming the obstacles posed by cytokines that suppress T cells in tumors, with the ultimate objective of stimulating further investigations for the development of novel therapeutic strategies to counteract their tumor-promoting activities.